2015
DOI: 10.1186/s12870-015-0459-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel system for evaluating drought–cold tolerance of grapevines using chlorophyll fluorescence

Abstract: BackgroundGrape production in continental climatic regions suffers from the combination of drought and cold stresses during winter. Developing a reliable system to simulate combined drought–cold stress and to determine physiological responses and regulatory mechanisms is important. Evaluating tolerance to combined stress at germplasm level is crucial to select parents for breeding grapevines.ResultsIn the present study, two species, namely, Vitis amurensis and V. vinifera cv. ‘Muscat Hamburg’, were used to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 46 publications
6
64
0
Order By: Relevance
“…Fourth and 5th leaf was used for estimating relative electrolyte leakage (REL) and relative water content (RWC), respectively. REL and RWC were determined as described previously (Su et al, 2015). The total RNA was isolated from the 3rd leaf for each treatment group at 15 days as described previously (Zheng et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth and 5th leaf was used for estimating relative electrolyte leakage (REL) and relative water content (RWC), respectively. REL and RWC were determined as described previously (Su et al, 2015). The total RNA was isolated from the 3rd leaf for each treatment group at 15 days as described previously (Zheng et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Every year, substantial loss of tea production and degradation of tea quality due to leaf senescence can result from a particular or often a combination of different stress conditions (Liu et al, 2015; Wang et al, 2016). In field conditions, cold stress often occurs in conjunction with drought stress, and this combination has been recognized as realistic threats faced by plants in the winter of semi-arid or drought-stricken areas (Su et al, 2015). Previously, a few notable studies demonstrated that stress interactions provoke altogether different signaling events and transcriptional responses that were unpredictable or not seen under either of the single stresses (Rasmussen et al, 2013; Pandey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The values of malondialdehyde (MDA) were determined by a thiobarbituric acid-based colorimetric method (Heath and Packer 1968). The values of electrolyte leakage (EL) were examined according to the method of Su et al (2015). Activities of antioxidant enzymes including superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), monodehydroascorbate reductase (MDHAR) and glutathione reductase (GR) were measured according to the method of Mostofa et al (2015).…”
Section: Measurement Of Photosynthetic Parametersmentioning
confidence: 99%
“…The combined actions of several stressors inflict more damage than each stress alone . For example, combined drought and heat stressors affect durum wheat growing in semi‐arid areas; in continental regions, grapevines are exposed to concurrent drought and cold stressors during winter . Although responses to single stressors, such as cold, drought, and heat, have been extensively investigated, relatively little is known about plant responses to multiple concurrent stressors .…”
Section: Discussionmentioning
confidence: 99%